2012
DOI: 10.1590/s1516-14392012005000166
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the rheological properties of crumb rubber modified bitumen and its correlation with temperature susceptibility

Abstract: There is substantial evidence on the advantages of using crumb rubber in enhancing conventional bitumen properties, gaining environmental protection and boosting industrial-economical benefits. Thus, the use of this ingenious additive in bitumen modification through sustainable technology is highly advocated.The main objective of this research is to investigate the effects of different blending conditions (of time and temperature) and various crumb rubber contents on the properties of bitumen binders. Testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…In addition, binders behave as elastic solids at lower temperatures suggestive of higher G ⁄ values. The trends of G ⁄ and d with respect to temperature confirmed the literature [5,6,8,9,12] in that modified CRMB and PMB binders showed higher G ⁄ and lower d than the virgin binders. Thus, it was concluded that modification of binders improves elasticity at high temperatures and improves flexibility at low temperatures.…”
Section: G ⁄ /Sind Binder Rutting Parameters and Predictive Modelssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, binders behave as elastic solids at lower temperatures suggestive of higher G ⁄ values. The trends of G ⁄ and d with respect to temperature confirmed the literature [5,6,8,9,12] in that modified CRMB and PMB binders showed higher G ⁄ and lower d than the virgin binders. Thus, it was concluded that modification of binders improves elasticity at high temperatures and improves flexibility at low temperatures.…”
Section: G ⁄ /Sind Binder Rutting Parameters and Predictive Modelssupporting
confidence: 86%
“…In addition, researchers [5][6][7][8][9][10][11][12] have also used advanced rheological binder characterization tests such as Dynamic Shear Rheometer (DSR), Bending Beam Rheometer, and Direct Tension tests on virgin, and rubber-and polymer-modified asphalt binders. These binder properties were later correlated with mixture properties to understand pavement performance from the rutting perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation also could be an important process which decides whether the expected performance of AR binders can be obtained or not and, during this process, the main concerning factors include mixing types, time and temperature [26][27][28][29]. AR binders mixed by a high-speed shear mixer performed better at low temperature while AR binders processed by a propeller-type mixer (low-speed mixer) had better intermediate and high-temperature performances and, also, were more resistant to fatigue cracking [29].…”
Section: Pe =mentioning
confidence: 99%
“…The longer mixing time and temperature could enable more IE and PE get established. Actually, compared with mixing temperature, the effect of mixing time could be limited, especially when the time exceeds 60 minutes, while a higher mixing temperature could increase complex shear modulus, elastic recovery, and ductility [26,30,31]. Briefly, the expected performance of AR binders could be obtained by reasonably controlling mixing parameters.…”
Section: Pe =mentioning
confidence: 99%
“…Therefore, to facilitate the evaluation of cooling rate sensitivity in controlled lab-scale conditions, the temperature of both pristine bitumen and bitumen modified with three additives was varied from 105 • C to 25 • C using cooling rates of 1, 5 and 10 • C/min, respectively. Being aware that the selected cooling rates might not exactly reproduce the realistic pavement conditions met in a field study, the purpose of this analysis was to gain a preliminary understanding of the impact that additives distinct from the most common polymers [9][10][11] may have on the bitumen rheological response to changes in the cooling rate. Therefore, a rheological investigation was performed to compare the mechanical behaviour manifested by a base bitumen modified with three additives, namely, organosilane (P2KA), polyphosphoric acid (PPA) and food grade phospholipids (LCS), whose properties as rheological/adhesion bitumen modifiers have been widely investigated [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%